The Nonlinear Interaction Between Monetary Policy and Financial Stress - Saldias, Martin (IMF Working Papers; Working Paper ;, 2017)
This paper analyzes the nonlinear relationship between monetary policy and financial stress and its effects on the transmission of shocks to output. Results from a Bayesian Threshold Vector Autoregression (TVAR) model show that the effects of monetary policy shocks on output growth are stronger during normal times than during times of financial stress. Monetary policy shocks are effective to ease stressed financial conditions, but have limited ability to fully contain the buildup of vulnerabilities. These results have important policy implications for central banks' countercyclical policies under different financial conditions and for 'lean against the wind' policies to address financial vulnerabilities.